A review of the game-based approaches to coaching literature in competitive team sport settings - Kinnerk, P.; Harvey, S.; MacDonncha, C.; Lyons, M. (Quest, 2018)
Game-Based Approaches (GBAs) have been advocated as a pedagogy to improve decision-making, skill execution, and physical fitness in physical education teaching and sports coaching. To date, no review paper has reported on the use of GBAs in competitive team sport settings. The purpose of this article was to review the research evidence conducted on GBAs specifically within competitive team sport settings and discuss the implications of these findings for sports coaching researchers and practitioners. The current review identified 23 articles investigating GBAs in competitive team sport settings. The review supports the efficacy of GBAs in the development of athlete decision-making and tactical awareness. GBAs promote personal and social development (e.g. player responsibility) along with positive affective outcomes for athletes (i.e. motivation, enjoyment). There was less support for the development of technical skill through GBAs. The review concludes by identifying future research directions and implications for competitive team sport coaches` practice.